2019
DOI: 10.1016/j.proci.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

An a priori analysis of a DNS database of turbulent lean premixed methane flames for LES with finite-rate chemistry

Abstract: An a priori analysis of a DNS database of turbulent lean premixed methane flames is presented considering the relative effects of turbulence and LES filtering, along with a potential modelling approach for LES with finite-rate chemistry. The leading-order effect was found to be due to the filter operation; flame response to turbulence was a secondary effect, and manifested primarily as an increase in standard deviations about conditional means. It was found that the radicals O, H and OH were less impacted by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…18 (blue) conditional upon bins of c for Δ∕d n = 0.03 and 0.15 in cases A, C, F of numerical errors because a posteriori assessment of models using LES is intrinsically code dependent as a result of the interaction of numerical and modelling errors (Vervisch et al 2008). It is worth noting that the same approach has been adopted in several previous studies (Ranjan et al 2016;Nilsson et al 2019;Reddy and Abraham 2012;Veynante et al 1997;Charlette et al 2002a;Selle and Bellan 2007;Lignell et al 2009;Chatakonda et al 2013;Lapointe and Blanquart 2017;Aspden et al 2019;Devaud et al 2019;Bushe et al 2020) by other authors and there are several examples where the models proposed based on a priori DNS analysis (e.g. Gao et al 2014a;Charlette et al 2002a) have been demonstrated to perform well based on a posteriori assessment (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…18 (blue) conditional upon bins of c for Δ∕d n = 0.03 and 0.15 in cases A, C, F of numerical errors because a posteriori assessment of models using LES is intrinsically code dependent as a result of the interaction of numerical and modelling errors (Vervisch et al 2008). It is worth noting that the same approach has been adopted in several previous studies (Ranjan et al 2016;Nilsson et al 2019;Reddy and Abraham 2012;Veynante et al 1997;Charlette et al 2002a;Selle and Bellan 2007;Lignell et al 2009;Chatakonda et al 2013;Lapointe and Blanquart 2017;Aspden et al 2019;Devaud et al 2019;Bushe et al 2020) by other authors and there are several examples where the models proposed based on a priori DNS analysis (e.g. Gao et al 2014a;Charlette et al 2002a) have been demonstrated to perform well based on a posteriori assessment (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…These findings were also confirmed using numerical simulations [6]. Since fuel oxidation involves a range of time-scales, its interaction with the multi-scale turbulent flow can alter the impact of specific reaction pathways [7]. Hence, the ability to determine this coupling between turbulence and ignition is essential for ensuring robust relight.…”
Section: Introductionmentioning
confidence: 73%
“…21 Combustion models such as the Flamelet/Progress Variable (FPV) 23 and dynamic Scale Similarity (SS) models 24 were a priori tested for nonpremixed turbulent flames. For turbulent premixed flames with finite-rate chemistry, Aspden et al 25 investigated the relative effects of turbulence and LES filtering and proposed a scaled reaction rates modeling approach based on filtered laminar flame profiles. For a non-conventional combustion regime, Chen et al 26 a priori assessed the capabilities of a machine learning (ML) tool, namely, the Deep Neural Network (DNN), to predict joint Filtered Density Functions (FDFs) of mixture fraction and reaction progress variable, and Iavarone et al 17 performed an a priori testing on the PaSR model performances, finding satisfactory results when specific characteristic time scales formulations are used.…”
mentioning
confidence: 99%